Pendampingan Perencanaan Jalan Raya Geometrik dan Tebal Perkerasan Lentur - Busnial Busnial; Oksy Rizky Rosadi; Peri Abdurahman (Universitas 45 Surabaya, 2025)
Highway geometric planning is an important part of road engineering that aims to create a safe, comfortable, and efficient path for road users. Community service activities in the form of education are one of the efforts to improve the quality of life of the community through providing useful understanding and skills. Observation is carried out using the interview method and direct observation in the field to identify problems faced by the community related to the planning and construction of neighborhood roads in the area. Based on the results of observations in the area targeted by the program, one of the work programs was determined, namely “Assistance in Geometric Highway Planning and Flexural Pavement Thickness in Sersan Bajuri, Lembang, Cihideung Village, Parongpong Sub-district, West Bandung Regency (KBB).” This program aims to provide the community with an understanding of the importance of environmental road planning in supporting accessibility and safety, including the planning process, selection of appropriate materials, understanding of structural elements, and application of plan drawings in the construction process.